Investigating Teachers’ Ethics in the Use of Social Media as a Teaching Media in EFL Classrooms : A Case Study at MAN 1 Kolaka Utara - Nursida Nursida; Ambo Dalle; Zulfah Zulfah; Magdahalena Tjalla; Mujahidah Mujahidah (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
offers various benefits, such as increased student engagement, flexible communication, and exposure to authentic materials. However, it also raises ethical challenges related to privacy, professionalism, and content responsibility. This study investigates how English teachers at MAN 1 Kolaka Utara reflect ethical awareness in using social media as a teaching tool. Employing a qualitative descriptive method, data were collected through interviews, observations, and document analysis involving four English teachers who actively used platforms like WhatsApp, Instagram, and YouTube. Thematic analysis revealed four central themes: ethical awareness, content selection, professional interaction, and student engagement. Findings suggest that while most teachers show commitment to ethical practices, such as respecting student privacy and maintaining professional boundaries, inconsistencies occur due to limited institutional guidelines. The study highlights the need for training and policy to support ethical digital pedagogy in EFL settings.